2010
DOI: 10.1007/s10750-010-0295-7
|View full text |Cite
|
Sign up to set email alerts
|

Similar distribution pattern of different phenotypes of Limnocythere inopinata (Baird) in a brackish-water lake in Inner Mongolia

Abstract: It has been recognized long ago that Limnocythere inopinata is a widely distributed ostracod and comprises various phenotypes. The taxonomy of the different phenotypes and their ecological differences, however, are still under debate. In this study, we investigated the relationships between ostracod distribution, water depth, and the substrate based on the analyses of species composition, abundance, and age structure of ostracods in 51 surface-sediment samples from Dali Lake in Inner Mongolia in order to revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 23 publications
0
16
1
Order By: Relevance
“…We did not sample the deepest part of Lake Dali (ca. 10 m depth, in the southwest of the lake), but an earlier investigation (Zhai et al, 2010) revealed that this area contain sparse populations of L. inopinata that are very rich in early juveniles and are deprived of adults. So it is likely that downslope contamination has influenced the whole profundal area of Lake Dali.…”
Section: Transport Of Limnocythere Inopinata In Lakesmentioning
confidence: 98%
See 2 more Smart Citations
“…We did not sample the deepest part of Lake Dali (ca. 10 m depth, in the southwest of the lake), but an earlier investigation (Zhai et al, 2010) revealed that this area contain sparse populations of L. inopinata that are very rich in early juveniles and are deprived of adults. So it is likely that downslope contamination has influenced the whole profundal area of Lake Dali.…”
Section: Transport Of Limnocythere Inopinata In Lakesmentioning
confidence: 98%
“…These 1-cm samples may cover the past one to three decades as estimated from the age-depth models of the sediment cores retrieved from these lakes (Xiao et al, 2004(Xiao et al, , 2008(Xiao et al, , 2009). In the laboratory, ostracod valves were extracted from freeze-dried samples following the method described by Zhai et al (2010Zhai et al ( , 2013, which used Na 2 CO 3 -buffered H 2 O 2 solution (pH 9-10) to disaggregate the sample before it was sieved and then pipetted onto some glass plates for microscopic examination. No distinction was made between the valves of 'living' and 'dead' specimens.…”
Section: Study Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytherissa lacustris, Limnocythere inopinata or Cyprideis torosa show smooth, punctuated, reticulated or noded carapaces (Fig. 4) depending on salinity range (Vesper 1975;Zhai et al 2010) and have rounded pores in freshwater environments, whereas irregular pores are present mainly in oligohaline to hypersaline waters. Rosenfeld and Vesper (1977) proposed a graphic diagram to calculate palaeosalinities based on percentages of round, elongate and irregular sieve pores of this species, which have been used in the palaeoenvironmental reconstruction of sediment cores (Gliozzi and Mazzini 1998).…”
Section: Ornamentationmentioning
confidence: 99%
“…The extraction of fossil ostracod valves followed the peroxide method described by Zhai et al [15]. We identified ostracods in the samples according to the taxonomy of Jiang et al [16], Meisch [17] and Hou et al [18].…”
Section: Methodsmentioning
confidence: 99%